Spatial reorganization of analytes in charged aqueous microdroplets. Issue 45 (24th October 2022) - Basuri, Pallab; Chakraborty, Amrita; Ahuja, Tripti; Mondal, Biswajit; Kumar, Jenifer Shantha; Pradeep, Thalappil
Abstract : Microscopic visualization of charged aqueous microdroplets reveals mass/size-selective segregation and spatial localization of solutes in the nanometer-thin air–water interface, along with the formation of micro–nano vacuoles at the droplet interior. Abstract : Imprinted charged aqueous droplets of micrometer dimensions containing spherical gold and silver nanoparticles, gold nanorods, proteins and simple molecules were visualized using dark-field and transmission electron microscopies. With such studies, we hoped to understand the unusual chemistry exhibited by microdroplets. These droplets with sizes in the range of 1–100 μm were formed using a home-built electrospray source with nitrogen as the nebulization gas. Several remarkable features such as mass/size-selective segregation and spatial localization of solutes in nanometer-thin regions of microdroplets were visualized, along with the formation of micro–nano vacuoles. Electrospray parameters such as distance between the spray tip and surface, voltage and nebulization gas pressure influenced particle distribution within the droplets. We relate these features to unusual phenomena such as the enhancement of rates of chemical reactions in microdroplets.